The Effect of Body Mass Index On Patellofemoral and Tibiofemoral Osteoarthritis in Postmenopausal Women - Burcu Yanık; Hakan Atalar; Aslı Köktener (Archives of Rheumatology, 2007)
Objective: Osteoarthritis is an important health problem with a multifactorial etiology. In this study, the effect of body mass index on patellofemoral and tibiofemoral osteoarthritis was investigated in 71 postmenopausal women. Patients and Methods: Ages of the patients were recorded. The body weight and height of the patients were measured and body mass indexes were calculated. Anterior-posterior radiographs were taken with knees extended bearing full weight; lateral radiographs evaluated according to the Kellgren-Lawrence scale were taken in the lateral decubitus position. Scores of 2 or greater were accepted as osteoarthritis. Totally 142 knees of 71 patients were examined. Generalized Estimating Equations statistical method was used for both tibiofemoral and patellofemoral osteoarthritis. Results: Mean values of the age of the patients were 64.4±8.5, and mean values of body mass indexes were 30 ± 5.2 idi. For each unit increase in body mass index, the increased likelihood of developing different OA traits (95% CI) was: tibiofemoral osteoarthritis 1.098 (1.006-1.1973) (P=0.0344) and patellofemoral osteoarthritis 1.096 (1.006- 1.1939) (P=0.0350). Conclusion: Obesity is an important risk factor for development of osteoarthritis at the tibiofemoral and patellofemoral joints of the knee. This emphasizes the potential importance of even minor weight reduction for prevention of knee osteoarthritis. (Rheumatism 2007; 22: 123-5)